Biodegradable stents for the treatment of benign stenoses of the small and large intestines - Rejchrt, S; Kopacova, M; Brozik, J; Bures, J (Endoscopy, 2011)
Biodegradable stents, which are made of various synthetic polymers, such as polylactide or polyglycolide, or co-polymers, such as polydioxanone, can be used for the treatment of benign refractory stenoses of the gastrointestinal tract. Here we report 11 patients (median age 41) with stenosing Crohn's disease of the small and/or large intestine. Endoscopic insertion of a biodegradable stent was successful at the first attempt in all patients except one. Subsequent follow-up was for a mean of 16 months, median 17 months, range 12-29 months. Early stent migration (between 2 days and 8 weeks) was seen in three patients. Mucosal overgrowth (epithelial hyperplasia) was not observed in any of the patients during the follow-up period. The high rate of early stent migration might be solved by appropriate tailoring and further improvements in the design of the biodegradable stents. Proof of long-term efficacy and safety requires further studies.
Keywords: stenty; kolon; Humans; selhání protézy; lidé středního věku; vstřebatelné implantáty; Female; dospělí; tenké střevo; Intestinal Diseases; Prospective Studies; výsledek terapie; Crohn Disease; Colon; lidé; nemoci střev; Absorbable Implants; Adult; Stents; Intestine, Small; Follow-Up Studies; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Crohnova nemoc; Prosthesis Failure; mužské pohlaví; prospektivní studie; Constriction, Pathologic; následné studie; stenóza